Emotional Eating- Theoretical Framework - Alshehri, Rasha Mohammed; Alrefae, Sabah; Alkhalaf, Arwa (Journal of Educational and Psychological Sciences, 2023)
The objective of this study aimed to clarify the meaning of the term emotional eating and the significant implications of its symptoms. Also, it highlighted the differences between emotional eating and Binge Eating Disorder, which shows some of the same symptoms. This study addressed the Causes of emotional eating, such as, environmental factors, high dietary restriction, low internal awareness, alexithymia, difficulties in emotional regulation, hypothalamic-pituitary-adrenal (HPA) axis dysregulation, which refers to a weakened cortisol response to stressors, negative parenting styles, and the interaction of depressive feelings with genetic predisposition. This study presented the most important theories and models that interpret emotional eating, including those focusing on physiological internal sensations, as well as those that explain it from the perspective of learning processes and cognitive operations. This is followed by a presentation of the most important previous studies in this field, which demonstrate the effectiveness of therapeutic programs in reducing emotional eating behavior through dealing well with negative emotions and changing maladaptive coping methods. Finally, in order to accurately determine the relationship between eating behavior and emotions, some of the relevant measures were presented.
Keywords: emotional eating; unconscious eating; emotional hunger; eating disorders; negative emotions; Emotional overeating